1999
DOI: 10.1364/ao.38.004891
|View full text |Cite
|
Sign up to set email alerts
|

Long-wavelength cutoff filters of a new type

Abstract: A method for the design of cutoff filters is proposed that is based on the use of light at nonnormal angles of incidence and on the use of coating materials with a large dispersion of the optical constants. The optical constants are presented of several films made from indium tin oxide--a material that satisfies this requirement. The filtering is due to absorption, critical angle effects, or both. The theory of this type of filter is described, and the calculated performance of two long-wavelength cutoff filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
2
13
1
Order By: Relevance
“…1(b). It was shown in our previous paper that there is very little polarization dependence of these curves in the cut-off and rejection regions [1]. Also indicated in this diagram is the expected transmittance of the system when the outer surfaces of the prisms are not provided with antireflection coatings.…”
Section: First Deposition Attemptmentioning
confidence: 72%
See 3 more Smart Citations
“…1(b). It was shown in our previous paper that there is very little polarization dependence of these curves in the cut-off and rejection regions [1]. Also indicated in this diagram is the expected transmittance of the system when the outer surfaces of the prisms are not provided with antireflection coatings.…”
Section: First Deposition Attemptmentioning
confidence: 72%
“…A tolerance analysis of our original ITO-based system indicated that the performance of the designs based on this principle would be very insensitive to film thickness variations but quite sensitive to variations in the optical constants [1]. Published data showed that the optical constants of ITO layers depend critically on the doping level and on the process used for their production.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Wavelength selective multiple interference filters are widespread in scien− ce and technology [3][4][5]. Their operation principles are well understood and implemented in commercial software [6].…”
Section: Introductionmentioning
confidence: 99%